2017
DOI: 10.1097/md.0000000000008319
|View full text |Cite
|
Sign up to set email alerts
|

ED50 of intrathecal ropivacaine for cesarean section under prophylactic infusion of phenylephrine

Abstract: Background:Studies have reported that prophylactic continuous infusion of phenylephrine during spinal anesthesia for cesarean section can decrease the spread of local anesthetics. We investigated the ED50 of intrathecal hyperbaric ropivacaine in parturient women undergoing cesarean section under prophylactic infusion of phenylephrine.Methods:Sixty parturient women were allocated into 2 groups in this prospective study. Group P received 0.5 mL kg−1 h−1 of phenylephrine (5 mg/50 mL) at the start of intrathecal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 14 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…In a previous study, we demonstrated that for lower limb surgery the MLAD values of 0.75% and 0.5% ropivacaine were 17.176 mg (0.75%) and 20.192 mg (0.5%) when using real-time UG SA to achieve a sensory blockade at the T10 level, while for LG SA the MLAD of ropivacaine was mostly between 7.6-12.8 mg (13)(14)(15)(16). Previous studies have also shown that the ED 50 of ropivacaine for reaching the T6 level of sensory block during cesarean sections under SA was 6.8-11.4 mg (27)(28)(29)(30), and the ED 50 of ropivacaine required to reach the T5 level was 5.92-8.35 mg (31). Kallio et al (32) studied inguinal hernia repair under SA and found that administering 15 mg of ropivacaine allowed 97% of patients to achieve a sensory block plane within 5-20 min of reaching above the T10 level, and also allowed them to remain above T10for 90 min.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous study, we demonstrated that for lower limb surgery the MLAD values of 0.75% and 0.5% ropivacaine were 17.176 mg (0.75%) and 20.192 mg (0.5%) when using real-time UG SA to achieve a sensory blockade at the T10 level, while for LG SA the MLAD of ropivacaine was mostly between 7.6-12.8 mg (13)(14)(15)(16). Previous studies have also shown that the ED 50 of ropivacaine for reaching the T6 level of sensory block during cesarean sections under SA was 6.8-11.4 mg (27)(28)(29)(30), and the ED 50 of ropivacaine required to reach the T5 level was 5.92-8.35 mg (31). Kallio et al (32) studied inguinal hernia repair under SA and found that administering 15 mg of ropivacaine allowed 97% of patients to achieve a sensory block plane within 5-20 min of reaching above the T10 level, and also allowed them to remain above T10for 90 min.…”
Section: Discussionmentioning
confidence: 89%
“…Moreover, Zhang et al compared the ED 50 of intrathecal ropivacaine when with or without phenylephrine infusion, and found a higher dose requirement when using phenylephrine infusion to prevent spinal-induced hypotension. [11] However, the optimum dose for clinical practice is 95% effective dose, which can meet 95% of patients’ analgesia requirement, rather than ED 50 . Additionally, phenylephrine is regarded as the first-line vasopressor for preventing spinal-induced hypotension in cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…[810] Moreover, one published study has demonstrated that the ED 50 of intrathecal ropivacaine for cesarean section with prophylactic infusion of phenylephrine was higher than without prophylactic infusion of phenylephrine. [11] In clinical practice, as we known, 95% effective dose (ED 95 , the dose is sufficient for 95% of patient to achieve effective anesthesia) is more meaningful than ED 50 for patients undergoing cesarean section. Therefore, in this study, we aimed to determine the ED 95 of intrathecal hyperbaric ropivacaine for patients undergoing cesarean section with intravenous prophylactic infusion of phenylephrine.…”
Section: Introductionmentioning
confidence: 99%
“…However there are some of disadvantages of SA including nausea, hemodynamic disorders such as hypotension [3]. Hypotension induced by SA is still a common complication [4], which might be up to 80% [5]. Such high incidence is the main limitation of SA in CS [6].…”
mentioning
confidence: 99%
“…Thus small dose of local anesthestic was advocated due to low incidence of hypotension induced by SA, however it possibly increased the failures [8,9]. In some cases phenylephrine has to be administered because of its' more advantages to prevent SA related to hypotension [5,10].…”
mentioning
confidence: 99%